“O caminho certo é a escola, é nossa porta de saída”: perspectivas e trajetórias de haitianos na UFSM - Troitinho, Bruna Ribeiro (2019)
The present research has as its theme the international migration whose research universe are Haitian students who joined the Federal University of Santa Maria (UFSM- Brazil), through Resolution No. 041/2016. The guiding question of this research is how do the trajectories of Haitian students emerge explanations about race relations in Brazil? The general objective is to describe the trajectories of these subjects and to analyze their impact on their perceptions of race relations in Brazil. The specific objectives are to (i) contextualize Haitian mobility and the education system, (ii) describe the space in which research is carried out, and (iii) analyze the trajectories linked to the explanations made by the research subjects about race relations in Brazil. Through an ethnographic study and semi-structured interviews, we sought to analyze the students' theories about race relations in Brazil. It was realized that previous experiences of migration ("I am traveling") coupled with Haitian nationalism are necessary factors to define the views of the interlocutors about racism in Brazil. According to their perspective, on the issue of race, Brazil presents itself as an alternative comparing itself with other countries of Haitian migration.